10.1k views
0 votes
Solve the quadratic by factoring. x² + 4x +1=6
Anyone know this one?
Thanks!​

User Henningst
by
4.6k points

2 Answers

3 votes

Answer:

X1=1 & X2=-5

Explanation:

x² + 4x +1=6

x² + 4x-5=0 % in standard condition

formula:

X1=(-b+sqrt(b²-4ac))/2a; X2=(-b-sqrt(b²-4ac))/2a;

so' Here

a=1 % co-efficient of x²

b=4 % co-efficient of x

c=-5 % constant

5 votes

Hi there! :)


\large\boxed{x = -5, 1}

x² + 4x + 1 = 6

Begin factoring by moving all terms to the left-hand side of the equation:

x² + 4x + 1 - 6 = 0

x² + 4x - 5 = 0

Factor by finding terms that SUM up to 4x and MULTIPLY into -5. We get:

(x + 5)(x - 1) = 0

Use the Zero-Product property to solve the quadratic equation:

x + 5 = 0

x = - 5

x - 1 = 0

x = 1

Therefore, the solutions are x = -5, 1.

User Newsha Nik
by
5.1k points